EFEKTIVITAS STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH MATERI TEOREMA PYTHAGORAS KELAS VIII SMP - Ananda Rizky Amelia; Ahmad Yani T; Dede Suratman (Universitas Tanjungpura, 2019)
AbstractThis study aimsed to determine the effectiveness of the index card matcj type active learning strategy in Pythagorean theorem material. The method used in this study was the experiment method and pre-experimental research with one-shot case study design. The effectiveness of learning the active learning strategy index card match type the implementation of learning, student activities and student learning outcomes. Data collection techniques used were measurements and observation sheets. The data collection tool used is are the student learning outcomes test, which contains 5 essay questions, observation sheets implementing learning and observation sheets for student activities. The research data were analyzed descriptively. The results of data analuzed obtained the implementation of learning with a good category,student activities classified as active and student learning outcomes are complete in a classical manner.Because all the effectiveness criteria are met, the active index card match type learning strategy in the Pythagorean theorem material is effectively used in class VII SMP N 12 Pontianak Keyword: Active Learning Strategy, Effectiveness Learning, Index Card Match, Pythgorean Theorem